2013
DOI: 10.4103/0970-9185.111680
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to evaluate the effect of intranasal dexmedetomidine versus oral alprazolam as a premedication agent in morbidly obese patients undergoing bariatric surgery

Abstract: Background:Morbidly obese patients with obstructive sleep apnea are extremely sensitive to sedative premedication. Intranasal dexmedetomidine is painless and quick acting. Intranasal dexmedetomidine can be used for premedication as it produces adequate sedation and also obtund hemodynamic response to laryngoscopy and tracheal intubation.Materials and Methods:Forty morbidly obese patients with BMI > 35 were chosen and divided into two groups. Group DEX received intranasal dexmedetomidine 1 mcg/kg (ideal body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
0
11
1
3
Order By: Relevance
“…If intravenous midazolam is used, obese patients should be closely monitored, with supplementary oxygen immediately available. Ketamine plus clonidine or dexmedetomidine are other options, with minimal adverse respiratory effects.…”
Section: Resultsmentioning
confidence: 99%
“…If intravenous midazolam is used, obese patients should be closely monitored, with supplementary oxygen immediately available. Ketamine plus clonidine or dexmedetomidine are other options, with minimal adverse respiratory effects.…”
Section: Resultsmentioning
confidence: 99%
“…DEX is a fast-acting alpha-2 adrenergic receptor agonist [ 1 2 3 4 7 8 ] with few adverse effects due to its short half-life [ 8 ]. Respiratory failure, which is a risk factor of most sedatives, occurs more often in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory failure, which is a risk factor of most sedatives, occurs more often in obese patients. Jayaraman et al [ 4 ] reported that there was no incidence of respiratory failure following sedation of obese patients using DEX. Use of sevoflurane in pediatric patients undergoing general anesthesia is associated with a high risk of emergence delirium; although it has been reported that the incidence of emergence delirium is lower when DEX is used [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan bir çalışmada OUAS hastalarında sedasyon amaçlı selektif alfa-2 adrenoreseptör agonisti deksmedetomidin kullanımınının solunum depresyonu yapmadığı bildirilmiştir 24 .…”
Section: Premedikasyonunclassified